Usulan Perbaikan Sistem Produksi Roti Manis Dengan Metode Statistical Quality Control Dan Failure Mode And Effect Analysis Di UMKM Dipo Bakery - Mukhtar Ahmad Swarnadi; Ayudyah Eka Apsari (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Dipo Bakery is a small and medium business engaged in the food sector, namely the sweet bread processing industry. The average number of production during October 2022 - March 2023 was 48,941.68 pcs, the average overproof defective product during October 2022 - March 2023 was 2,688.16 pcs, the average defective product size did not match during October 2022 - March 2023 as many as 4,949.33. Statistical Quality Control is a technique used in controlling and managing both manufacturing and service processes using statistical methods. Failure Mode and Effect Analysis (FMEA) to find out the main causes of product defects and provide appropriate improvement suggestions. Based on the results obtained, it shows that there is no data that crosses the upper control limit (UCL) for overproof defects at 0.168844 and for defects of unsuitable size at 0.251876 as well as the lower control limit (LCL) for overproof defects. at point – 0,. So, it can be concluded that the damage to the production process of the sweet bread variant is still under control within the control limits. obtained the highest RPN value of 105 with the cause of haste.